2009
DOI: 10.1261/rna.1499309
|View full text |Cite
|
Sign up to set email alerts
|

A fast selenium derivatization strategy for crystallization and phasing of RNA structures

Abstract: Site-specific 29-methylseleno RNA labeling is a promising tool for tackling the phase problem in RNA crystallography. We have developed an efficient strategy for crystallization and structure determination of RNA and RNA/protein complexes based on preliminary crystallization screening of 29-OCH 3 -modified RNA sequences, prior to the replacement of 29-OCH 3 groups with their 29-SeCH 3 counterparts. The method exploits the similar crystallization properties of 29-OCH 3 -and 29-SeCH 3 -modified RNAs and has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
54
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 35 publications
2
54
0
Order By: Relevance
“…Very recently, Ennifar and co-workers [45] have demonstrated that the 2'-OMe modification can be used for RNA-crystallization screening, considering the current high cost of Se derivatization. After identification of the crystallization conditions, the 2'-OMe group will be replaced with the 2'-SeMe functionality for the derivatization.…”
Section: 22mentioning
confidence: 99%
See 2 more Smart Citations
“…Very recently, Ennifar and co-workers [45] have demonstrated that the 2'-OMe modification can be used for RNA-crystallization screening, considering the current high cost of Se derivatization. After identification of the crystallization conditions, the 2'-OMe group will be replaced with the 2'-SeMe functionality for the derivatization.…”
Section: 22mentioning
confidence: 99%
“…After identification of the crystallization conditions, the 2'-OMe group will be replaced with the 2'-SeMe functionality for the derivatization. In this work [45], U266, U267, and U270 sites of the DIS stem RNA were derivatized and screened. As a result, they found that the 2'-OMe and 2'-SeMe derivatized RNAs were comparable in terms of crystallization behavior and diffraction property.…”
Section: 22mentioning
confidence: 99%
See 1 more Smart Citation
“…Inspired by the convenient Se-derivatization of proteins, since 1998, Huang's research group has pioneered and developed the selenium derivatization of nucleic acids for X-ray crystallography (Carrasco et al 2001;Caton-Williams and Huang 2008;. We found that the selenium-derivatized RNAs and DNAs are stable and that the selenium derivatizations do not cause significant perturbation Salon et al 2007Salon et al , 2010Sheng et al 2007Sheng et al , 2011Caton-Williams and Huang 2008;Olieric et al 2009;Hassan et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a series of selenium-containing nucleosides and oligonucleotides have been used for convenient phasing of X-ray crystallographic data. [11][12][13] Some methylseleno nucleosides were found to inhibit prostatic cancer cells growth. [14] Selenium has not been found in DNA, although its presence in natural uridines from tRNAs has been documented.…”
Section: Introductionmentioning
confidence: 99%